Analysis of Water Quality in the Winto River, Buton, Southeast Sulawesi - Arini Rajab; Fachruddin Azwari; Kemala Hadidjah; Martha E. Siahaya; Adi Supriadi; Christine Elia Benedicta; Christopaul Palalangan Toding Layuk; Andi Gita Tenri Sumpala (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study assessed the water quality of the Winto River in Buton Regency, Southeast Sulawesi, at upstream and downstream points adjacent to asphalt mining activities. Sampling was carried out in accordance with SNI 8995:2021, and the results were evaluated by comparing the physical, chemical, heavy metal, and biological parameters against river water quality standards for classes 1 to 4 as stipulated in Government Regulation No. 22 of 2021. Findings revealed that physical, chemical, and biological parameters generally remained within safe limits. The measurement results show that the water temperature is maintained at a constant 28 °C and is still within the permissible deviation. TDS and TSS values were low, pH was neutral, and both BOD and COD indicated minimal organic loads. Nutrients and heavy metals were well below permissible thresholds, while total coliform counts complied with Class 1 standards. These results suggest that the Winto River has not yet experienced significant water quality degradation despite its proximity to asphalt mining. The novelty of this research lies in providing empirical evidence from a rarely studied context in Indonesia, serving as an essential baseline for long-term monitoring. Practically, the findings highlight the need for continuous monitoring and for evidence-based policies by local authorities to ensure sustainable water resource management in mining-affected regions